The diet of Gull-billed Tern Gelochelidon nilotica breeding in the Po Delta (NE Italy) - Roberto G. Valle; Francesco Fava (Rivista Italiana di Ornitologia - Research in Ornithology)
The present study provides the first data on the diet of Gull-billed Terns (Gelochelidon nilotica) nesting in the Po Delta. Four hundred and forty-five prey items were found in pellets collected on a colony in a fish farm on June 11, 2018. Pellets contained mostly Invertebrata (403 items), of which the majority were Insecta (50.8%, mainly Orthoptera: 22.7%) and, to a lesser extent, Crustacea (22%, exclusively Red Swamp Crayfish Procambarus clarkii) and Mollusca (17.8%, mostly Gasteropoda: 16.2%), whereas Vertebrata accounted for only 9.4% (42 items, mostly Amphibia: 8.3%). Gull-billed Terns nesting in the Po Delta follow a diet with a predominance of Insecta, but with significant shares of Crustacea and Mollusca and, to a lesser extent, Amphibia, thus confirming the flexibility of the species in adapting to the prey availability of the foraging area.